2021
DOI: 10.1111/age.13053
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of fleece traits in Inner Mongolia Cashmere goats

Abstract: Inner Mongolia Cashmere goat is a well-known local cashmere goat breed in China. It is famous for excellent fleece quality and a significant advantage in cashmere yield compared to other cashmere goat breeds. In this study, a genome-wide association study was used to investigate fiber length, fiber diameter, and cashmere yield of 192 Inner Mongolia Cashmere goats using the Illumina GoatSNP52K Beadchip panel. We discovered that four single nucleotide polymorphisms (SNPs) reached genome-wide significance levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Lv et al [ 108 ] reported a regulating role of FGF12 gene in the sheep hair follicle development process. In addition, our finding supported by Wang et al [ 109 ] study that reported the role of FGF12 gene in hair follicle development in cashmere goats. The SLC7A11 gene (CNVR_Chr7:73.54–73.57 Mb) is an amino acid transporter which mediates the extracellular cysteine in exchange for glutamate [ 110 ].…”
Section: Discussionsupporting
confidence: 91%
“…Lv et al [ 108 ] reported a regulating role of FGF12 gene in the sheep hair follicle development process. In addition, our finding supported by Wang et al [ 109 ] study that reported the role of FGF12 gene in hair follicle development in cashmere goats. The SLC7A11 gene (CNVR_Chr7:73.54–73.57 Mb) is an amino acid transporter which mediates the extracellular cysteine in exchange for glutamate [ 110 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, significant associations with body weight, growth-related and body conformation traits were identified by GWAS in 150 Dazu Black goats [ 18 ], in 95 Sudanese goats [ 28 ], in 69 Egyptian Barki sheep [ 33 ], and in 96 Baluchi sheep [ 34 ]. Genome-wide associations with other economic important traits were found in sample sizes of 192 animals [ 35 , 36 ]. In this regard, we believe that it possible to use a sample of 269 animals for our research.…”
Section: Discussionmentioning
confidence: 99%
“…The quantile-quantile plots (Q-Q plots) and Manhattan plots from GWAS analyses were produced using the ggplot2 in the R package. The suggestive genome-wide association significance threshold was p<1.20×10 −6 (0.05/41784), and the chromosome-wide significance level threshold was p<3.58×10 −5 (0.05/41784/30), as referred to Wang et al [ 11 ]. The most significant SNPs per trait were selected as the lead SNPs, and the candidate genes were further searched.…”
Section: Methodsmentioning
confidence: 98%
“…litter size [ 3 , 4 ] and nipple number [ 5 7 ], morphological traits, e.g. coat color [ 8 ], skin color [ 9 , 10 ], wool [ 11 , 12 ], and wattle [ 13 ] in different sheep and goat breeds by GWAS, which has led to the identification of different candidate genes or SNPs. However, the lack of consistency among these findings has suggested the complexity of the genetic basis of these traits.…”
Section: Introductionmentioning
confidence: 99%